Gambaran Korban Kekerasan Seksual di Rumah Sakit Bhayangkara Tingkat III Manado Tahun 2024 - Siregar, Mahatop A.; Mallo, Nola T. S.; Tomuka, Djemi (Universitas Sam Ratulangi, 2026)
Abstract: Sexual violence carries numerous negative impacts and tends to increase, even though underreporting remains high. This study aimed to describe the characteristics of sexual violence victims at Bhayangkara Hospital Level III Manado in 2024. This was a descriptive retrospective study with a cross-sectional design using secondary data obtained from Visum et Repertum. The results identified 314 cases of sexual violence in year 2024. The majority of cases were female victims (98.4%) and aged 13–17 years (58.6%). Based on victims’ addresses, majority of victims came from North Minahasa Regency (42%), while Tuminting District was the most common origin in Manado (7.6%). The highest percentages were found in students as the occupational group (89.2%), boyfriends as the perpetrators in terms of social relationship with the victims (38.9%), underwent examination more than 72 hours after the incident (64.3%), lacerations as the injury type (77.2%), old hymenal tears (84.7%), and hymen as the most frequent injury site (77%). In conclusion, the majority of victims are students aged 13–17 years. The high number of sexual violence cases needs to be intervened in order to reduce the rate of sexual violence, such as: early age sexual education and outreach for reporting when experiencing sexual violence to reduce the negative impact of the incident. Keywords: sexual violence; fornication; rape Abstrak: Kekerasan seksual memiliki banyak dampak negatif dan cenderung mengalami peningkatan meskipun under reporting masih tinggi. Penelitian ini bertujuan untuk mengetahui gambaran korban kekerasan seksual di Rumah Sakit Bhayangkara Tk. III Manado tahun 2024. Jenis penelitian ialah deskriptif retrospektif dengan desain potong lintang menggunakan data sekunder dari hasil Visum et Repertum. Hasil penelitian mendapatkan 314 kasus kekerasan seksual pada tahun 2024. Mayoritas korban kasus kekerasan seksual berjenis kelamin perempuan (98,4%), berada pada rentang usia 13-17 tahun (58,6%). Alamat korban terbanyak berasal dari Kabupaten Minahasa Utara (42%) dan Kecamatan Tuminting di Kota Manado (7,6%). Persentase tertinggi didapatkan pada pekerjaan sebagai pelajar (89,2%), pacar sebagai hubungan sosial antara korban dengan pelaku (38,9%), korban diperiksa setelah >72 jam setelah kekerasan seksual terjadi (64,3%), terdapat luka robek (77,2%), robekan lama pada hymen (84,7%), dan hymen sebagai lokasi luka yang paling banyak ditemukan (77%). Simpulan penelitian ini ialah kasus kekerasan seksual kebanyakan pelajar dan rentang usia 13-17 tahun. Tingginya kasus kekerasan seksual perlu untuk diintervensi agar menekan angka kekerasan seksual, seperti: pendidikan seksual usia dini dan penyuluhan untuk pelaporan ketika mengalami kekerasan seksual untuk mengurangi dampak negatif dari peristiwa itu. Kata kunci: kekerasan seksual; percabulan; pemerkosaan